Why should we invest in health? Evidence from the lens of second-order benefits of health - Delfin Lovelina Francis; Neha Dumka; Atul Kotwal; Dutta PK (Inishmore Laser Scientific Publishing Ltd, 2023)
Life expectancy and access to health care have both increased globally in recent decades, and these innovations have significantly improved well-being. As a result, health reforms are increasingly becoming a top concern in all countries in order to address/increase accessibility, affordability, and availability of quality services, as well as improve spending efficiencies. There are many evidenced benefits which are secondary to the health benefits of those programmes. However, second-order benefits of health schemes have received little attention and are rarely discussed in mainstream policy and practice. The paper intends to contribute to broader initiatives to recognise health schemes as vital in achieving equitable and inclusive development that benefits the entire community. The logical framework technique was used to analyse the health schemes' second-order benefits. The primary and secondary objectives, methods, outcomes, and impacts were compared. Apart from the health programmes' own objectives, the analysis revealed extensive benefits such as employment opportunities, local partnerships with communities, decreased inequalities and population-level impacts on socio-economic development, women empowerment, increase in literacy and school completion rates, and decrease in out-of-pocket expenditure. The economic impact of investing in health systems by creating high-quality jobs and purchasing goods and services from local businesses is highlighted by the second-order health advantages, which are in relation to the primary benefits. Not only do healthcare systems play an important role in the economies of the nation, but also in the social lives of these communities.